Herpes zoster – is there a need for new treatment recommendations? - Karić, Uroš; Katanić, Nataša; Peruničić, Sanja; Mitrović, Nikola; Nikolić, Nataša; Marković, Marko; Bojović, Ksenija; Malinić, Jovan; Poluga, Jasmina; Simonović Babić, Jasmina (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. The reactivation of the varicella zoster virus results in herpes zoster. Acyclovir is currently recommended over 7 to 10 days for herpes zoster treatment and should be started within 72 hours of rash eruption. This study analyses whether a therapy delay and/or shorter courses of treatment are associated with adverse outcomes. Methods. We identified 292 patients treated at the Clinic for Infectious and Tropical Diseases in Belgrade for herpes zoster in a five-years period. The data on these patients were analyzed using the descriptive statistics, the χ2 test, the Mann-Whitney U-test and the multiple logistic regression analysis. Results. The average time from rash eruption to the first dose of acyclovir was 4.07 ± 2.64 days. The patients received acyclovir for 6.83 ± 2.45 days. Seventy-one patients had disseminated herpes zoster, 100 had cranial nerve involvement, 86 had complications other than postherpetic neuralgia and one patient died. In cases where therapy was delayed there was no significant association with complications (χ2 = 0.031; p = 0.86). Our logistic regression model was not able to predict who was treated less than 7 days. An association between the HZ complications and abbreviated acyclovir regimens was not demonstrated (χ2 = 1.109; p = 0.326). We conducted the PubMed search on February 1st, 2017 and found no proof for the need to apply at least 7 days of acyclovir therapy for herpes zoster in the studies that have been published so far. Conclusion. We were unable to prove an association between therapy delay and unfavorable outcomes. The same was true for shorter than recommended acyclovir courses.